Palmitic Acid Promotes Virus Replication in Fish Cell by Modulating Autophagy Flux and TBK1-IRF3/7 Pathway - Yu, Yepin; Li, Chen; Liu, Jiaxin; Zhu, Fengyi; Wei, Shina; Huang, Youhua; Huang, Xiaohong; Qin, Qiwei (Frontiers in Immunology, 2020)
Palmitic acid, or hexadecanoic acid, is the most common saturated fatty acid in animals, plants and microorganisms. Studies highlighted that palmitic acid plays significant roles in regulating diverse cellular processes and virus infections. Accumulation of palmitic acid in fish cells (grouper spleen, GS) infected with Singapore grouper iridovirus (SGIV) was evaluated through lipid metabolic profiles and fluorescence microscopy. The fluctuated content levels after virus infection suggested that palmitic acid was functional in virus-cell interactions. To investigate the roles of palmitic acid in SGIV infection, the effects of palmitic acid on cytopathic effect, expression levels of viral genes and viral proteins, as well as viral products were evaluated. The infection and replication of SGIV were increased after exogenous addition of palmitic acid, but inhibited by knockdown of fatty acid synthase (FASN), of which the main function was to catalyze palmitate synthesis. In addition, the promotion of virus replication was associated with the down-regulating of interferon-related molecules, and the reduction of IFN and ISRE promotor activities by palmitic acid. Furthermore, we discovered that palmitic acid restricted TBK1, but not MDA5-induced interferon immune responses. On the other hand, palmitic acid decreased autophagy flux in GS cells through its dual effects on suppressing autophagic degradation and inhibiting AKT-mTOR signaling, and subsequently enhanced viral replication. Together, our findings indicated that the palmitic acid not only functioned as a negative regulator of TBK1-IRF3/7 pathway, but also a suppressor of autophagic flux, and finally promoted the replication of SGIV in fish cells.